Relationship between Loneliness and Internet Addiction During The COVID-19 Pandemic on Class XI Students of 99 Jakarta Public High School Even Semester in The Academic Year 2021/2022 and Its Review from Islamic View - Misae Fattah Rizki; Sri Hastuti Andayani (Junior Medical Journal, 2023)
When WHO stated that one way to prevent transmission of COVID-19 is social distancing, the Government of Indonesia carried out a large-scale social restriction program (PSBB), namely work from home, distance learning/learning from home (school from home), and carrying out worship activities from home. Those programs can lead to a lack of social interaction in students' social life cause an increase in loneliness during a pandemic. Individuals who feel lonely will look for ways to fill their emptiness, including the internet. The internet can be a place of escape or coping for many lonely individuals that can form an online friendship, which can cause reducing loneliness despite the excessive use that can turn into an addiction. This study aims to determine the relationship between loneliness and internet addiction during the COVID-19 pandemic in Class XI students at SMA Negeri 99 Jakarta in the even semester of the 2021/2022 academic year. This study used an observational study with a cross-sectional that conducted by students at age 15-18 years old. The results of the analysis of the relationship between loneliness and internet addiction show a correlation coefficient (r) = 0.418 and a significance value of 0.000 (p 0.05), which concludes loneliness has a significant effect on internet addiction. This study concludes that there is a positive correlation between the two variables, where the higher the loneliness, the higher the level of internet addiction.